Manifestação do Darwinismo Social na Eugenia e suas implicações para o ensino de Ciências e Biologia - Monteiro, Flávia Leite (Universidade Federal de São Carlos, 2021)
Since the beginnings of society, forms of segregation and hierarchization among peoples have been naturalized by human beings. With the development of modern science, scientific arguments that could justify the marginalization of certain groups in society began to be sought. In this context, Social Darwinism and its aspects, including eugenics, have been emerged. Eugenicist thinking preaches that there is an ideal eugenic type, and that, through artificial selection, it would be possible to improve the human being. The eugenics movement was very strong during the first decades of the 20th century; however, it is a mistake to believe that the eugenic discourse is no longer reproduced today. The current work seeks to understand to what extent the critical approach to eugenic discussions in science and biology classes can contribute to overcoming attempts to naturalize sociocultural prejudices. For this end, the role of critical education in the area of science was discussed, and how important it is to break with the ideal of neutral and unattainable science. Phrases from recognized authors were also selected through interviews in newspapers and magazines, original books by these authors and scientific articles. After this, the phrases were subdivided into four categories: genetic determinism, geographic determinism, hygienism and scientific racism. The chosen methodology was qualitative research, through documentary research, to carry out the analysis of the author's discourse on a sociocultural view of genetics and evolution. The explanatory limits of these phrases were worked throughout the work using concepts of genetics and evolution to counteract the eugenic ideas contained in them, trying to interpret it within the cultural context in which the sentence was emitted. With the development of the work, it can be concluded that working with eugenics in the classroom is one of the ways to contextualize teaching and can help to overcome prejudices, transforming the reality of the student, a fundamental step in exercising a critical education.
Manifestation of Social Darwinism in Eugenics and its Implications for the teaching of Science and Biology
Keywords: Ensino; Genética; Teaching; Genetics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM